2018
DOI: 10.1016/j.cobeha.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of vertebrate survival circuits

Abstract: Evolution selects those adaptive features that increase reproductive probabilities and facilitate survival. Analysing the brain circuits mediating risk-avoidance (e.g. defense) and those allowing reward-seeking (motivated) behaviours in different vertebrates leads to several main conclusions. First, circuits mediating risk-avoidance are similar in all studied vertebrates, where they include amygdala homologues located in the posterior half of the cerebral hemispheres, in close relationship with the chemosensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 87 publications
5
13
0
Order By: Relevance
“…The arcopallium is a large, heterogenous brain region, but we are beginning to understand the contribution of its individual subdivisions to the regulation of fear-related behaviours 10 . Our findings support the proposal that the dorsal arcopallium is homologous to a part of the BLA based on developmental studies 11,12,29 . The lateral nidopallium is also proposed to be partially homologous to the BLA based on a detailed analysis of the embryonic origin and gene expression profile 11,12,29 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The arcopallium is a large, heterogenous brain region, but we are beginning to understand the contribution of its individual subdivisions to the regulation of fear-related behaviours 10 . Our findings support the proposal that the dorsal arcopallium is homologous to a part of the BLA based on developmental studies 11,12,29 . The lateral nidopallium is also proposed to be partially homologous to the BLA based on a detailed analysis of the embryonic origin and gene expression profile 11,12,29 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support the proposal that the dorsal arcopallium is homologous to a part of the BLA based on developmental studies 11,12,29 . The lateral nidopallium is also proposed to be partially homologous to the BLA based on a detailed analysis of the embryonic origin and gene expression profile 11,12,29 . Our data showed that 5-HTR4 was preferentially expressed in the dorsal arcopallium (Figs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations